Prediction of pile running during the driving process of large diameter pipe piles. (1st December 2016) - Sun, Liqiang; Jia, Tianqiang; Yan, Shuwang; Guo, Wei; Ren, Yuxiao; Lei, Zhenming
Abstract: Offshore platforms in deep seas require extremely long large diameter pipe piles (LDPPs) to support the loads generated from the structure itself, wind and waves. One of the construction issues related to the installation of a LDPP into a seabed is pile running. Unexpected pile running during the LDPP driving process may break the steel wires connected to the heavy hammer or may cause the loss of the hammer into the sea. An analytical method to predict the occurrence of pile running is proposed in this paper. The framework for determining the calculation parameters from a laboratory or field test are established. The dynamic resistance of the surrounding soil during the pile driving process is considered through analysis of the soil sensitivity and the induced excess pore water pressure. Three case studies were conducted to verify the accuracy of the proposed method. Good agreement indicated that the proposed method is capable of predicting pile running during the driving process of LDPPs in layered soil deposits. Highlights: All the comments from the reviewer are carefully addressed. The English of this paper has been revised by Elsevier Webshop. The whole paper was reorganized.